EGFR and c-MET Cooperate to Enhance Resistance to PARP Inhibitors in Hepatocellular Carcinoma - Qiongzhu Dong (5156150) (2019)
PARP1 inhibitors (PARPi) are currently used in the clinic for the treatment of ovarian and breast cancers, yet their therapeutic efficacy against hepatocellular carcinoma (HCC) has been disappointing. To ensure therapeutic efficacy of PARPi against HCC, a disease often diagnosed at intermediate to advanced stages with no effective treatment options, it is critical to identify not only biomarkers to predict PARPi resistance but also rational treatments to overcome this. Here, we report that a heterodimer of EGFR and MET interacts with and phosphorylates Y907 of PARP1 in the nucleus, which contributes to PARPi resistance. Inhibition of both EGFR and MET sensitized HCC cells to PARPi, and both EGFR and MET are known to be overexpressed in HCC. This report provides an explanation for the poor efficacy of PARPi against HCC and suggests combinatorial treatment consisting of EGFR, MET, and PARP inhibitors may be an effective therapeutic strategy in HCC. Significance: Regulation of PARP by the c-MET and EGFR heterodimer suggests a potentially effective combination therapy to sensitize HCC to PARPi. Other Information Published in: Cancer Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1158/0008-5472.can-18-1273